New Results for Boundary Layer Flow and Convection Heat Transfer Over a Flat Plate by Using the Homotopy Perturbation Method - Mehran Khaki JAMEI; Mehdi KHAZAYINEJAD; Davood Domairry GANJI (Walailak Journal of Science and Technology, 2013)
This work presents a boundary-layer analysis of an incompressible viscous steady flow and forced convection over a horizontal flat plate. The solution for velocity and temperature are calculated by applying the Homotopy perturbation method (HPM). A special technique is attempted by which one is able to obtain solutions that are close to the exact solution of the equation. The obtained results are compared to the exact solution and another results provided by previous works so that the high accuracy of the obtained results is clear. Also, the results reveal that this method is effective, simple, and can be applied for other nonlinear problems in different fields of science and engineering, especially some fluid mechanics and heat transfer equations.